Digital Competitiveness through TERM for Student-Entrepreneurs in Central Java - Jati Nugroho; Bagus Yunianto Wibowo; Andi Setiawan; M Nahar; Noor Suroija (International Journal of Technology and Education Research, 2025)
Digital competitiveness has become a critical factor for entrepreneurial success in the modern economy. This article examines how the Techno-Entrepreneurial Relationship Marketing (TERM) model can enhance the digital competitiveness of student entrepreneurs in Central Java. Using a mixed-methods approach, the study assesses the impact of digital tools, entrepreneurial orientation, and proactive market engagement on business outcomes. The findings reveal that TERM significantly improves digital marketing performance, customer loyalty, and competitive positioning by fostering data-driven decision-making, rapid responsiveness, and personalized customer interactions. The study highlights the importance of integrating TERM into entrepreneurship education to prepare students for the challenges of the digital economy. It concludes with practical recommendations for educators, policymakers, and student entrepreneurs on how to leverage TERM to achieve long-term business sustainability and competitive advantage in a rapidly evolving digital marketplace. These insights are particularly relevant for institutions seeking to develop the next generation of innovative, tech-savvy entrepreneurs.